2014
DOI: 10.1590/1982-021620149613
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do dimorfismo sexual e da relação entre as características craniofaciais, dos arcos dentários e do músculo masseter na fase de dentição mista

Abstract: Purpose: to evaluate sexual dimorphism and the relationship between craniofacial characteristics, dental arch morphology and masseter muscle thickness in children in the mixed dentition stage. Methods: the study sample comprised 32 children, aged 6-10 years (14♀/18♂) with normal occlusion. Craniofacial characteristics, dental morphology and masseter muscle thickness were evaluated by means of posteroanterior cephalometric radiographs, dental cast evaluation and ultrasound exam, respectively. The results were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The results of this study are similar to those of Generosos' et al, Marquizin et al, and Liu' et al studies. [24][25][26] Generoso et al conducted a study on 40 male and 40 female puberty ages in Brazil. It revealed that the male mandibular length was greater than that of female in various malocclusion classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study are similar to those of Generosos' et al, Marquizin et al, and Liu' et al studies. [24][25][26] Generoso et al conducted a study on 40 male and 40 female puberty ages in Brazil. It revealed that the male mandibular length was greater than that of female in various malocclusion classes.…”
Section: Discussionmentioning
confidence: 99%
“…24 The longitudinal studies conducted by Weber et al in a Caucasian race sample aged 16-18 years showed that the male mandibular length was longer than that of females. 25 The size of the mandible in female over the age of 14 years is relatively constant, whereas in male it is still increasing. 24,25 The longitudinal studies conducted by Liu et in 48 samples consisting of 24 females and 24 Caucasian race males showed that there were significant differences in mandibular size between males and females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also supported by previous studies of He et al 25 and Kiliaridis et al 26 who reported that reduced activity of the masseter muscle resulted in thin muscle fibres. However, a previous study by Raadsheer et al 24 in 1999 reported greater thickness on the left side, whereas Raadsheer et al 5 and Marquezin et al 27 found no side differences in the thickness of the muscle in subjects with normal occlusion.…”
Section: Discussionmentioning
confidence: 85%